Environmental sustainability in shipper-LSP relationships - Anu Bask; Mervi Rajahonka; Sini Laari; Tomi Solakivi; Juuso Töyli; Lauri Ojala (Elsevier, 2022)
In this study we examine the role of environmental sustainability in transport operations in Shipper-Logistics Service Provider (LSP) relationships from the LSP perspective. The research questions posed are as follows: What kinds of firm see environmental sustainability as a component of competitive advantage, and why? How does environmental sustainability manifest itself in firm operations, and why? What pressures are there for environmentally sustainable development, and why? What is the role of environmental sustainability in the selection of LSPs, and why? Data was collected from Finland, using an exceptional combination involving both quantitative and qualitative methods in a survey (600 responses) and in firm interviews (15 LSPs). The findings indicate that large, globally-operating shippers and carriers are the most interested in environmental issues, partly because of external pressures and partly because they see the greening of transport as a potential source of competitive advantage. However, due to the lack of widely accepted methods for measuring the environmental impact of transports, companies cannot easily share the costs and benefits of environmental initiatives between supply chain members nor use such initiatives as marketing arguments to differentiate their offerings. Therefore, environmental sustainability acts in practice more as an order qualifier than as an order winner in the carrier selection process. Despite this, it seems that environmentally proactive LSPs financially outperform their less active peers. We therefore conclude that environmental sustainability can be free, if it is integrated with operational performance and cost indicators that boost competitive advantage. Our study contributes to the intersection of GSCM and logistics, particularly from the LSP point of view.